THE CONCEPTUAL QUALITY EVALUATION OF THE INFORMATION CIRCULATING IN TECHNICAL-ORGANIZATIONAL SYSTEMS - Gennady A. Berketov; Andrey A. Mikrukov; Anatolij I. Polous (Открытое образование (Москва))
The article discusses the approach to assessing the quality of the information obtained in the process of transformation of the initial information received by control signals in the organizational and technical systems, control solutions, make up the content management process. The essence of the approach is to assess the quality of the information offered on its quantitative characteristics (the relative amount of syntactic, semantic and pragmatic information types are in relationships and relationships).